2004
DOI: 10.1007/s00147-004-0739-y
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in long-term graft survival in cadaveric renal transplant recipients treated with mycophenolate mofetil

Abstract: Though mycophenolate mofetil has markedly reduced the incidence of acute rejection in renal transplantation, a significant improvement in graft survival has been more difficult to demonstrate. This retrospective study compares an historical control group of 210 consecutive renal transplant patients, who had received ATG induction associated with cyclosporin, prednisolone and azathioprine, with 187 patients receiving mycophenolate instead of azathioprine. The incidence of acute rejection was decreased with myco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
1
1
0
Order By: Relevance
“…According to our results, switching from AZA to MMF as rescue therapy after acute rejection can avoid the negative impact of rejection on long-term graft survival. This is consistent with previous studies where MMF in addition to reducing the acute rejection rate also improved the prognostic significance of these rejection episodes (13). One of the possible mechanisms may be that MMF prevents development of chronic allograft nephropathy independent of acute rejections.…”
Section: Successful Rescue Therapy With Mycophenolate Mofetil In Kidnsupporting
confidence: 92%
“…According to our results, switching from AZA to MMF as rescue therapy after acute rejection can avoid the negative impact of rejection on long-term graft survival. This is consistent with previous studies where MMF in addition to reducing the acute rejection rate also improved the prognostic significance of these rejection episodes (13). One of the possible mechanisms may be that MMF prevents development of chronic allograft nephropathy independent of acute rejections.…”
Section: Successful Rescue Therapy With Mycophenolate Mofetil In Kidnsupporting
confidence: 92%
“…Post‐transplant changes in renal function, hepatic metabolism, enterohepatic recycling, albumin levels, concomitant medication as well as variations in hepatic uridinediphosphate glucuronosyl transferase (UGT) expression lead to the highly variable pharmacokinetics reported in a number of studies [4–8]. Several studies have addressed the correlation between MPA concentrations and clinical outcome in renal transplantation and shown that MPA concentrations correlate with acute rejections [9–11]. However, trough MPA has shown to be of poorer predictive value than MPA AUC [11,12].…”
Section: Introductionmentioning
confidence: 99%